Performance of PID controller for engine speed controller using CVT - Wan Hazmin, Wan Osman (2010)
This project is a simulation and experimental investigation into the development of PID controller using MATLAB SIMULINK software. The simulation development of the PID controller with the mathematical model of DC motor is done using Ziegler-Nichols method and trial and error method. The PID parameters are to be tested with an actual motor also with the PID controller in MATLAB/SIMULINK software. In order to implement the PID controller from the software to the actual DC motor data acquisition is used. From the simulation and the experiment, the result performance of the PID controller is compared in term of response and the assessment is presented. CVT transmission firstly designed using the Solid Work software to know the mechanical system and the dimension of this transmission. Then, the mathematical calculation is done to know the criteria DC Motor to be selected and the exact rotation of the motor as primary source to the transmission. The motor must be capable to produce 4.14N.m or more of torque in order to mechanism to function perfectly until it reach it limit.the DC motor should rotate only in 16.12rad or 2.57 rotation.Therefore PID controller are used to achieve this value in the simulation. After using the trial and error metod in order to decided the exact value for costant value of Kp=15, Ki=25 and Kd=0.15 in PID controller system to ensure the DC motor is rotated in 16.12rad.